2010
DOI: 10.1016/j.neuron.2010.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Switch in Sensory Processing Prepares Developing Neocortex for Vision

Abstract: Developing cortex generates endogenous activity that modulates the formation of functional units, but how this activity is altered to support mature function is poorly understood. Using recordings from the visual cortex of preterm human infants and neonatal rats, we report a novel “bursting” period of visual responsiveness during which the weak retinal output is amplified by endogenous network oscillations, enabling a primitive form of vision. This period ends shortly before delivery in humans and eye-opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
266
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(290 citation statements)
references
References 95 publications
22
266
1
1
Order By: Relevance
“…4h). In summary, the electrophysiological characteristics of Ca 2 þ clusters agree well with those of previously reported spindle bursts in the visual cortex of neonatal rats [50][51][52] . Although the aforementioned measurements were acquired through the intact dura after surgical removal of the overlying bone, virtually identical Ca 2 þ cluster activity was observed through the intact skull (n ¼ 3 mice; Supplementary Fig.…”
Section: Gaba-evoked Cats In Presence Of Bayk 8644 At P3-4supporting
confidence: 89%
“…4h). In summary, the electrophysiological characteristics of Ca 2 þ clusters agree well with those of previously reported spindle bursts in the visual cortex of neonatal rats [50][51][52] . Although the aforementioned measurements were acquired through the intact dura after surgical removal of the overlying bone, virtually identical Ca 2 þ cluster activity was observed through the intact skull (n ¼ 3 mice; Supplementary Fig.…”
Section: Gaba-evoked Cats In Presence Of Bayk 8644 At P3-4supporting
confidence: 89%
“…We interpret visual processing as instantaneous because we are incapable of detecting a time interval less than 40 ms. Any two events that are separated by less than 40 ms appear as happening simultaneously [35], suggesting that there is a lag time in which processing must take place before one can perceive anything externally. This supports our theory in that as these biochemical processes take place, the images are projected directly into the brain through pre-existing oscillations that allow the retina and brain to communicate in real-time, because this neural network was formed in utero [36][37][38][39].…”
Section: Phototransductionsupporting
confidence: 75%
“…Prior hypotheses suggest they could play a part in forming maps for ''orientation, direction, and ocular dominance" prior to vision [37], while experimental data has indicated that retinal waves develop early on, are critical in the developing visual system interconnections, and help prepare the circuitry required for visuomotor learning and behavior [45]. In humans, spontaneous retinal activity is generated by retinal neurons before vision takes place, creating functional maps in higher visual areas [37,38,46]. The supposition is that retinal development and subsequent retinal waves link together the lateral geniculate body and cortex, thereby being a major contributor in the formation of an ''internal" neural space which forms the infrastructure of visual consciousness.…”
Section: Visual Circuitsmentioning
confidence: 99%
“…The use of several frequency bands is reasoned by the previous studies in adults showing that the spatial extent of an oscillation is proportional to its temporal frequency (Freeman, 2005). In neonatal EEG, the highest frequency range (> 10 Hz) is likely most relevant (Colonnese et al, 2010;Vanhatalo et al, 2005).…”
Section: Hdeeg Experimentsmentioning
confidence: 99%